2004
DOI: 10.1016/s0002-9440(10)63156-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased DNA Methyltransferase 1 (DNMT1) Protein Expression Correlates Significantly with Poorer Tumor Differentiation and Frequent DNA Hypermethylation of Multiple CpG Islands in Gastric Cancers

Abstract: We evaluated the significance of aberrant DNA methyltransferase 1 (DNMT1) protein expression during gastric carcinogenesis. The protein expression of DNMT1, Muc2, human gastric mucin, E-cadherin, and proliferating cell nuclear antigen was examined immunohistochemically in gastric cancers and corresponding noncancerous mucosae from 134 patients. The DNA methylation status of the CpG islands of the p16, human MutL homologue 1 (hMLH1), E-cadherin, and thrombospondin-1 (THBS-1) genes and the methylated in tumor (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
180
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(189 citation statements)
references
References 37 publications
9
180
0
Order By: Relevance
“…To discriminate definitively positive samples from samples with background staining, if Ͼ 30% of the cells in a tissue sample exhibited nuclear staining, then the sample was categorized with positive immunoreactivity. 16 Among the 46 MEC samples, 29 samples (63%) were positive for DNMT1. Correlations between the incidence of nuclear immunoreactivity for DNMT1 and the clinicopathologic features of patients with MEC are shown in Table 1.…”
Section: E-cadherin and Dnmt1 Stainingmentioning
confidence: 99%
“…To discriminate definitively positive samples from samples with background staining, if Ͼ 30% of the cells in a tissue sample exhibited nuclear staining, then the sample was categorized with positive immunoreactivity. 16 Among the 46 MEC samples, 29 samples (63%) were positive for DNMT1. Correlations between the incidence of nuclear immunoreactivity for DNMT1 and the clinicopathologic features of patients with MEC are shown in Table 1.…”
Section: E-cadherin and Dnmt1 Stainingmentioning
confidence: 99%
“…The most abundant of these is DNMT1, which is primarily responsible for maintenance and regulation of DNA methylation patterns, while DNMT3A and DNMT3B establish de novo methylation patterns which are then maintained by DNMT1 (Jones and Baylin, 2002;Okano et al, 1999). Previous studies have shown that significant increased expression of DNMT1 protein positively correlates with the hypermethylation status of CpG islands of several genes in gastric cancers, including p16, human MutL homologue 1 (hMLH1), CDH1, and thrombospondin-1 (THBS1) (Etoh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The gene instability in gastric cancer including gene amplification, loss of heterozygosity (Sano et al, 1991) or microsatellite instability (Fang et al, 2003) may cause the inactivation of some tumor-suppressor genes, such as p53, and deregulation of some signaling molecules so as to enhance some signaling pathways, such as Wnt or Ras-dependent mitogen-activated protein kinase (MAPK) pathway, which may promote the tumorigenesis (Kim et al, 1991;Clements et al, 2002;Stock and Otto, 2005). In another way, the gene silencing in gastric cancer frequently results from promoter hypermethylation caused by overexpression of DNA methyltransferase 1 and involves many genes expression such as hMLH1, E-cadherin, transforming growth factor (TGF)-b receptor type I and RUNX3 that loss of them may exacerbate the gastric cancer progression (Etoh et al, 2004;Stock and Otto, 2005;Sato and Meltzer, 2006). The more comprehensive investigations of molecular mechanisms related to gastric carcinogenesis will provide more evidences for developing novel diagnostic and therapeutic strategies against gastric cancer.…”
Section: Introductionmentioning
confidence: 99%